2000
DOI: 10.1002/(sici)1097-4628(20000124)75:4<495::aid-app4>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis and NMR studies of methyl methacrylate (MMA)-methacrylic acid copolymers synthesized by an unusual polymerization of MMA

Abstract: Methyl methacrylate-methacrylic acid (MMA-MAA) copolymers were prepared from the polymerization reaction of the methyl methacrylate (MMA) monomer with concentrated nitric acid (65% HNO 3 ) at different reaction times in the absence of other reagents in the reaction mixture. The hydrolysis degrees of the MMA-MAA (sodium salts) copolymers estimated by thermogravimetry (TG) corroborated the data obtained by chemical titration. By calorimetry (DSC), a relationship between the glass transition temperature (T g ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…After heating, the signal for the tert -butyl CH 3 groups has decreased in intensity and the quaternary carbon signal has almost disappeared. If carboxylic acid groups are formed, the corresponding carbonyl signal should be observed more downfield around 180 ppm . The spectra do not reveal such signals.…”
Section: Thermal Analysismentioning
confidence: 95%
“…After heating, the signal for the tert -butyl CH 3 groups has decreased in intensity and the quaternary carbon signal has almost disappeared. If carboxylic acid groups are formed, the corresponding carbonyl signal should be observed more downfield around 180 ppm . The spectra do not reveal such signals.…”
Section: Thermal Analysismentioning
confidence: 95%
“…For example, the T g of the polymer binder (M25-S25-I50-P0) was 154.58C, whereas that of another binder (M25-S25-I0-P50) was 212.68C. The T g of pure poly(MAA), poly(STY), poly(IBMA), and poly(PMI-co-STY) were 166, 97, 180, and 2258C, respectively, as obtained from literature [19][20][21][22]. The results showed that T g increased with the PMI content due to the rigid characteristics of the PMI molecular structure.…”
Section: Glass Transition Temperaturementioning
confidence: 82%
“…The properties of acrylic copolymers, such as their photosensitivity [5], thermal stability [6][7][8][9][10][11][12], pattern resolution [9,13], glass transition temperature [14], nanosilica modified [8,[15][16][17], and physical characteristics [18], have been investigated in negative-type photoresists. The T g values of pure poly(methacrylic acid), polystyrene, poly(isobornyl methacrylate), and poly(phenylmaleimide-costyrene) were obtained from literature [19][20][21][22]. However, the preparation and thermal properties of four-component copolymers have not been studied sufficiently.…”
Section: Introduction T Hin-film Transistor Liquid Crystal Displays (mentioning
confidence: 99%
“…Copolymerization with monomers that can form hydrogen bonds with the carbonyl groups of PMMA such as acrylamide (AM), methacrylamide (MAAM), acrylic acid (AA), or methacrylic acid (MAA) was another efficient method to raise the T g of PMMA . However, water absorbability of the copolymers increased because of the existence of polarity groups of —CONH 2 or —COOH.…”
Section: Introductionmentioning
confidence: 99%